Optimization of internal psychological climate of project teams as a way to increase the competitiveness of an enterprise - Филатов, Антон Сергеевич; Хрутьба, Виктория Александровна (Technology audit and production reserves, 2013)
The object of the research is the formation of a project team to enhance the competitiveness of enterprises. The subject of the research is the formation of the internal psychological climate of project teams. The purpose of this research is to develop a mechanism to optimize the internal psychological climate in project teams for the effective use of human resources based on the analysis of the features of the socionic environment itself as well as on the analysis of the intensity of the poles that form this environment (i.e. what the percentage of each pole are Reinin Criterion (RC) is). The author has defined the main problems associated with general psychological environment in the team, with the processes of information exchange in the community at the intersection of various disciplines: project management, socionics and information science. Using knowledge of these disciplines helps to create decision support system for project managers. The computer program "Lad" can be applied by project managers and project team members to develop a strategy and tactics of the optimization of the internal psychological climate in the team in order to solve effectively their specific tasks. Knowledge of the characteristics of communication within a particular group helps both to effectively combine people in a working environment and to create specific groups for different purposes: for long-term cooperation, for "brainstorming", etc. The author has suggested an approach to optimize the internal psychological climate of a team for efficient use of human resources with the computer program "Lad."